Merealisasikan Gerakan Semangat Belajar Bahasa Inggris Anak-anak Panti Asuhan - Tuti Atika; Fatimah Zahara (Yayasan Literasi Sains Indonesia, 2022)
Technological advances have made the ability to speak English very important. This is because the use of English is no longer just for greeting, but also for other needs to support activities. Even if you don't have plans to travel or study abroad, English is still a priority to learn. Because, now the world has entered a digital era filled with advances in information technology. The digital era makes the world seem borderless because of the distance and time that seem to be connected via the internet. Not a bit of information in cyberspace is presented in English, this is what makes the ability to master one of these international languages ​​very important to have. By having an English qualification that is recognized worldwide, the opportunities in the future will be wide open. However, there are still many Indonesians who have low English skills, especially those from underprivileged groups such as orphans. Therefore, this practical activity is a very targeted thing to do. The process of providing assistance is also carried out in street vendors' mini project activities, using the casework method through the general intervention stage consisting of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. The focus of the client's problem solving process is learning to write, read and memorize as a jointly designed strategy to increase the client's interest in learning. The objectives of this program were also stated to be achieved, as evidenced by the increased enthusiasm for learning and the client's greater curiosity about all kinds of knowledge. In addition, there was an increase in their reading and speaking skills and their motivation in learning English. In addition, this program also provides benefits for both parties who participate socially and educationally. This means that there is a positive impact after the implementation of this program.